Take me out to the ball game - Fertig, Dennis; McMahon, William Franklin (Niles, Ill. : A. Whitman, 1987)
Describes in text and photographs a young boy's experiences as he attends his first major league baseball game at Chicago's Wrigley Field with his father.
13
Keywords: Baseball -- Illinois -- Chicago; Baseball -- Illinois -- Chicago -- Juvenile literature